AN ANALYSIS OF WAQF MANAGEMENT IN TERMS OF WAQF LAW NO. 41 YEAR 2004 (Study on Waqf Management by Branch Head of Muhammadiyah 1 to 13 Banjarmasin) - MAIRIJANI, MAIRIJANI (At-Taradhi Jurnal Studi Ekonomi, 2015)
Abstract: In some countries, waqf isused as media for walfare of people. It is also possible to be implemented in Indonesia, where the majority of its population is Muslim, if properly managed waqf. The government issued a regulation that Law No. 41 Year 2004 on Waqf in an attempt to achieve these expectations. The method used in this research is a juridical approach, analyzing the management of waqf held by PCM (Branch Head of Muhammadiyah) 1 to 13 Banjarmasin in perspective Law No.41 Year 2004 on Waqf. Muhammadiyah is one of nadzir with legal form in accordance to the Decree of the Minister of Home Affairs No. SK 14/DDA/1972 on appointment Muhammadiyah as a legal entity, therefore Muhammadiyah Central, Regional and Branch entitled appointed as nadzir, including Branches Head of Muhammadiyah in Banjarmasin. Nadzir responsibility is to manage the assets of waqf, either by registering waqfassets as well as develop the waqf assets and expansion waqf assets through productive business. Based on the result of the research, it is illustrated that from 88 waqf assets in all Branches Head of Muhammadiyah Banjarmasin only 41 assets that registered in the name of Muhammadiyah. The development of the existing assets still consumptive, such as mosque, maqbarah, and others, it should be developed through productive business, for example built of?ces, outlets, pharmacies, hotels, conference halls, home industries, and plantations. In fact there is an opportunity for Branches Head of Muhammadiyah to manage HTR (Plantation Forest), the funding provided by the Government in the revolving loan fund, which ultimately waqf assets is not only bene?cial but can also be a source offunds (fundraising).